Implementation of restorative justice in medical dispute resolution - Ummi Maskanah (Universitas Aisyah Pringsewu, 2023)
In Indonesia, medical disputes can result in criminal prosecution, despite the private nature of the relationship between patients and medical personnel. This is to safeguard the public from non-standard medical practices. Infractions of the regulations governing standard medical treatment procedures and requirements for acquiring medical personnel can result in criminal penalties. Occasionally, however, criminal penalties are not applied and a restorative justice approach is used in trials. This study seeks to examine the application of restorative justice in the resolution of medical disputes. This is a normative legal study that investigates secondary data. The research findings indicate that the implementation of restorative justice in Indonesia is already a part of the nation's culture through the use of problem-solving discussions. Nonetheless, the essence of the justice system in Indonesia tends to be retributive, that is, it emphasizes retribution over justice. Generally, medical disputes can be avoided if the doctor-patient relationship is maintained correctly, informed consent is obtained, and standard procedures are followed. In Indonesia, medical disputes are typically resolved legally by filing reports with the Indonesian Medical Discipline Honorary Council (abbreviated MKDKI), filing civil lawsuits or pursuing compensation, and filing criminal reports. In this paper, the author argues that restorative justice is an effective method for resolving medical disputes due to its emphasis on recovery, the nature of medical disputes, which are generally not the result of deliberate actions, the nature of criminal law as an ultimatum remidium, and restorative justice's status as a paradigm of contemporary criminal law.Abstrak: Di Indonesia, sengketa medis dapat berujung pada tuntutan pidana, meskipun hubungan antara pasien dan tenaga medis bersifat privat. Hal ini untuk melindungi masyarakat dari praktik medis yang tidak standar. Pelanggaran peraturan yang mengatur standar prosedur perawatan medis dan persyaratan untuk memperoleh tenaga medis dapat mengakibatkan hukuman pidana. Namun, kadang-kadang, hukuman pidana tidak diterapkan dan pendekatan keadilan restoratif digunakan dalam persidangan. Penelitian ini berusaha mengkaji penerapan keadilan restoratif dalam penyelesaian sengketa medis. Ini adalah studi hukum normatif yang menyelidiki data sekunder. Hasil penelitian menunjukkan bahwa implementasi restorative justice di Indonesia sudah menjadi bagian dari budaya bangsa melalui penggunaan diskusi pemecahan masalah. Meskipun demikian, esensi sistem peradilan di Indonesia cenderung bersifat retributif, yaitu lebih mengutamakan retribusi di atas keadilan. Umumnya, perselisihan medis dapat dihindari jika hubungan dokter-pasien dipertahankan dengan benar, persetujuan diperoleh, dan prosedur standar diikuti. Di Indonesia, sengketa medis biasanya diselesaikan secara hukum dengan mengajukan laporan kepada Majelis Kehormatan Disiplin Kedokteran Indonesia (disingkat MKDKI), mengajukan gugatan perdata atau mengejar ganti rugi, dan mengajukan laporan pidana. Dalam tulisan ini, penulis berpendapat bahwa keadilan restoratif merupakan metode yang efektif untuk menyelesaikan sengketa medis karena penekanannya pada pemulihan, sifat sengketa medis, yang pada umumnya bukan merupakan hasil dari tindakan kesengajaan, sifat hukum pidana sebagai ultimatum remidium , dan status keadilan restoratif sebagai paradigma hukum pidana kontemporer.